Schyłek kanonii akademickich w krakowskiej Kapitule katedralnej? - Urban, Jacek (Analecta Cracoviensia, 2008)
The Jagiellonian restoration of the University of Cracow, founded in 1364, took place in 1400. Besides the legacy of Queen Hedwig and King Wladysław Jagiełło, Piotr Wysz, the Bishop of Cracow, donated to the University two canonries in the Wawel Cathedral Chapter. Since then, the University nominated candidates to these offices thus providing them with the necessary financial support. They were called the academic canonries and the designated professors - the academic canons. Even during the time when the nobility usurped the exclusive right to nominate canons, two seats in the Chapter were always reserved for the University. The Senate of the University presented the candidates to the canonries for more than 500 years. The article deals with the academic canonries after 1945, especially in the time of the communist regime. The Senate of the Jagiellonian University exercised its law to nominate the canons for the last time in 1951. In 1954, the communist authorities removed the 550 years old Department of Theology from the University. The Author discusses the initiatives, in particular those of Cardinal Karol Wojtyła, aiming to maintain the principle that the Department of Theology be represented in the Cathedral Chapter by two of its professors.